Teknik Isolasi dan Identifikasi Bakteri Pekasam Ikan Gabus (Chana Striata) - Khalim Purnomo; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Pekasam is a traditional fermented fish product that involves microbial activity, particularly lactic acid bacteria, during its fermentation process. This study aims to isolate and identify bacterial species involved in the fermentation of gabus fish (Channa striata). Samples were collected at different stages of fermentation and analyzed microbiologically. The isolation procedure utilized selective media such as MRS agar and Nutrient Agar (NA). The resulting colonies were observed based on morphology and further identified through biochemical tests, Gram staining, and oxidase tests. The results indicated the dominance of several bacterial isolates, primarily from the Lactobacillus genus. Identification confirmed that lactic acid bacteria played a crucial role in the fermentation process and contributed to the characteristic flavor of the pekasam. This research contributes to the scientific understanding of traditional fish fermentation and offers potential for utilizing local probiotic strains in traditional food products.